Multi -Perspectives evaluation and benchmarking of real-time sign language recognition systems based on fuzzy multi-criteria decision analysis - Al-Samarraay, Mohammed S. Mahmoud (Tanjong Malim, 2022)
Multi -Perspectives evaluation and benchmarking of real-time sign language recognition systems based on fuzzy multi-criteria decision analysis by Al-Samarraay, Mohammed S. Mahmoud